Image Quality and Related Outcomes of the ShuntScope-Guided Catheter Implantation in Adult Hydrocephalus: Experience of 63 Procedures - Prajsnar-Borak, Anna; Teping, Fritz; Oertel, Joachim (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Ventricular catheter (VC) placement in the selected subset of adult hydrocephalus can be highly challenging due to abnormal anatomical configuration or the need for trans-aqueductal stent placement. Transluminal endoscopy with the ShuntScope has been invented to increase the success rate of catheter placement. This study evaluates the image qualities of ShuntScope and related surgical outcomes in adults.Methods A retrospective analysis of all adult patients undergoing VC placement using the ShuntScope from November 2011 to July 2022 in the authors' department was performed. Demographic, clinical, and radiologic data were evaluated. The visualization quality of the intraoperative endoscopy was stratified into excellent, medium, and poor, and compared to the postoperative catheter tip placement. Follow-up evaluation included the surgical revision rate due to proximal catheter misplacement.Results A total of 63 ShuntScope-assisted surgeries have been performed on 60 adults. The mean age of the patients was 48.43 years. The most common underlying pathology was a tumor- or cyst-related cerebrospinal fluid (CSF) impairment in 38.33%, followed by a pseudotumor cerebri in 21.66%. The achieved image quality was excellent in 39.68%, medium in 47.62%, and poor in 12.7%. Ideal catheter placement was achieved in 79.37%. There were no intraoperative complications associated with the use of the ShuntScope. The revision rate due to suboptimal proximal VC placement was 4.76% during a mean follow-up period of 27.75 months. A statistical correlation between the image quality and accuracy of the catheter position was observed (p < 0.001).Conclusion The ShuntScope can be considered an important addition to standard surgical tools in treating a selected subset of adult hydrocephalus. Direct visualization might even help achieve correct placement of the catheter in the cases with blurred vision and limited visual overview.
Keywords: ShuntScope; hydrocephalus; endoscopy; ventricular catheter; shunting